Role of micronutrition in patients with oral cancer and nutritional intervention strategies - Fan, Yunwei; Feng, Yuling; Liu, Wenxin (Frontiers in Nutrition, 2025)
Oral cavity cancer exhibits high mortality rates with conventional therapies often causing nutritional complications. Emerging evidence highlights the critical role of micronutrients in modulating oxidative stress, a key driver of carcinogenesis in precancerous lesions including oral lichen planus, leukoplakia and submucous fibrosis. Zinc deficiency impairs antioxidant defenses while copper excess promotes angiogenesis. Selenium maintains redox balance through selenoproteins and vitamins A, E and C exhibit chemopreventive effects through reactive oxygen species scavenging and immunomodulation. Immunonutrition strategies incorporating omega-3 fatty acids and arginine demonstrate benefits in postoperative outcomes. This review summarizes the mechanistic roles of antioxidant micronutrients including zinc, copper, selenium and vitamins A, D, E, C and B complex in oral squamous cell carcinoma pathogenesis and explores personalized nutritional interventions to enhance treatment tolerance and quality of life. Optimizing micronutrient status represents a promising adjuvant approach in comprehensive oral cancer management.